THE CHALLENGES OF WEIBO FOR DATA-DRIVEN DIGITAL MEDIA RESEARCH - Zeng, Jing; Burgess, Jean; Bruns, Axel (AoIR Selected Papers of Internet Research, 2015)
Data generated via user activity on social media platforms is routinely used for research across a wide range of social sciences and humanities disciplines. The availability of data through the Twitter APIs in particular has afforded new modes of research, including in media and communication studies; however, there are practical and political issues with gaining access to such data, and with the consequences of how that access is controlled. In their paper ‘Easy Data, Hard Data’, Burgess and Bruns (2015) discuss both the practical and political aspects of Twitter data as they relate to academic research, describing how communication research has been enabled, shaped and constrained by Twitter’s “regimes of access” to data, the politics of data use, and emerging economies of data exchange. This conceptual model, including the ‘easy data, hard data’ formulation, can also be applied to Sina Weibo. In this paper, we build on this model to explore the practical and political challenges and opportunities associated with the ‘regimes of access’ to Weibo data, and their consequences for digital media and communication studies. We argue that in the Chinese context, the politics of data access can be even more complicated than in the case of Twitter, which makes scientific research relying on large social data from this platform more challenging in some ways, but potentially richer and more rewarding in others.